Caries risk assessment. A systematic review. (February 2014) - Mejàre, I.; Axelsson, S.; Dahlén, G.; Espelid, I.; Norlund, A.; Tranæus, S.; Twetman, S.
Abstract Objective. To assess the ability of multivariate models and single factors to correctly identify future caries development in pre-school children and schoolchildren/adolescents. Study design. A systematic literature search for relevant papers was conducted with pre-determined inclusion criteria. Abstracts and full-text articles were assessed independently by two reviewers. The quality of studies was graded according to the QUADAS tool. The quality of evidence of models and single predictors was assessed using the GRADE approach. Results. Ninety original articles fulfilled the inclusion criteria. Seven studies had high quality, 35 moderate and the rest poor quality. The accuracy of multivariate models was higher for pre-school children than for schoolchildren/adolescents. However, the models had seldom been validated in independent populations, making their accuracy uncertain. Of the single predictors, baseline caries experience had moderate/good accuracy in pre-school children and limited accuracy in schoolchildren/adolescents. The period of highest risk for caries incidence in permanent teeth was the first few years after tooth eruption. In general, the quality of evidence was limited. Conclusions. Multivariate models and baseline caries prevalence performed better in pre-school children than in schoolchildren/adolescents. Baseline caries prevalence was the most accurate single predictor in all age groups. The heterogeneity of populations, models, outcome criteria, measures and reporting hampered the synthesis of results. There is a great need to standardize study design, outcome measures and reporting of data in studies on caries risk assessment. The accuracy of prediction models should be validated in at least one independent population.